Jaminan Gadai dalam Akad Rahn di Pegadaian Syariah Sampang - Mohammad Mohammad; Insana Meliya DCA Sari (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2022)
The study aims to find out the arrangements for pawning collateral in the rahn contract at the Sampang Sharia Pawnshop Unit Robatal and the mechanism for handling auctions in rahn guarantees at the Sampang Sharia Pawnshop Unit Robatal. It is empirical research, so obtaining the data is done by observation and interviews. The results of this study are twofold. First, Islam allows debt agreements, which are the essence of a pawn agreement. This pawn agreement in Islamic law is a